(untitled) (Bangladesh Journal of Botany, 2025)
Rumex dentatus, is commonly controlled using metsulfuron-methyl, a sulfonylurea herbicide, in wheat. However, lower efficacy of metsulfuron-methyl against R. dentatus was observed at some places in Haryana. Hence, a well-structured questionnaires-based survey was conducted in Haryana during rabi 2018-19 to understand the current-status and factors determining metsulfuron-methyl resistance against R. dentatus, among 120 farmers from three districts. The present study revealed a decrease in farmers’ use of metsulfuron-methyl from 61.1 (2016-17) to 23.8% (2018-19), while metribuzin usage increased from 6.49 to 41.27%. The herbicide dose used by farmers increased from 0.99 to 1.16 times of X-dose from 2016-17 to 2018-19 to control R. dentatus. The highest percent-control of R. dentatus was recorded with 2,4-D (83-92%) and lowest for metsulfuron-methyl (69-72%). Over 90% farmers utilized 60-180 L water acre-1 while only 6.7% were used standard volume of water (200 L/acre) during spray. Only 19.2% farmers used standard flat-fan nozzle but the rest used flood jet/cut-nozzle. Most farmers (>80%) adopted delayed herbicide application while only 15.8% farmers applied herbicide at standard time (30-35 DAS). All these factors could be associated with reduced herbicide efficacy against R. dentatus. Over 50% of farmers used herbicides with similar modes of action, and 75% follow only rice-wheat crop rotation. Farmers’ liking for herbicide was 2,4-D, metribuzin, clodinafop+metribuzin and last metsulfuron-methyl. The present-study revealed challenges in controlling R. dentatus in Haryana, particularly with metsulfuron-methyl. To avoid resistance development, it recommends reducing the usage of single-herbicides while advocating the rotational application of herbicides with proper spray techniques. Bangladesh J. Bot. 54(2): 269-276, 2025 (June)